The Enlightenment and science in eighteenth-century France - Kiernan, C (Voltaire Foundation, 2017)
Foreword Introduction Chapter 1. Deism and science Chapter 2. Atheism and science Chapter 3. Progress and science Chapter 4. Government and science Chapter 5. The Debate on science Chapter 6. Chemistry Chapter 7. Biology Conclusion Select bibliography Index